The monument - Paulsen, Gary. (Delacorte Press, 1991)
Thirteen-year-old Rocky, self-conscious about the braces on her leg, has her life changed by the remarkable artist who comes to her small Kansas town to design a war memorial.
Thirteen-year-old Rocky, self-conscious about the braces on her leg, has her life changed by the remarkable artist who comes to her small Kansas town to design a war memorial.